2003
DOI: 10.1073/pnas.0305665101
|View full text |Cite
|
Sign up to set email alerts
|

Entropic switch regulates myristate exposure in the HIV-1 matrix protein

Abstract: The myristoylated matrix protein (myr-MA) of HIV functions as a regulator of intracellular localization, targeting the Gag precursor polyprotein to lipid rafts in the plasma membrane during virus assembly and dissociating from the membrane during infectivity for nuclear targeting of the preintegration complex. Membrane release is triggered by proteolytic cleavage of Gag, and it has, until now, been believed that proteolysis induces a conformational change in myr-MA that sequesters the myristyl group. NMR studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
504
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 296 publications
(541 citation statements)
references
References 66 publications
(52 reference statements)
35
504
2
Order By: Relevance
“…One would therefore predict that addition of the CA domain, which contains additional multimerization signals, should promote myristate exposure at lower protein concentrations than myrMA. This is exactly what Tang et al (11) found. The monomer 7 trimer equilibrium constant is 20 times higher for myrMA-CA than for myrMA.…”
supporting
confidence: 77%
“…One would therefore predict that addition of the CA domain, which contains additional multimerization signals, should promote myristate exposure at lower protein concentrations than myrMA. This is exactly what Tang et al (11) found. The monomer 7 trimer equilibrium constant is 20 times higher for myrMA-CA than for myrMA.…”
supporting
confidence: 77%
“…NOEs between the myristate group and the side chains of Val-7 and Leu-8 were also observed for the WT myrMA protein. 27 These NMR observations indicate that mutation of Arg-7 and Leu-8 does not greatly alter the conformation of the loop and that residues 7 and 8 play an important role into the stabilization of the myr(s) form.…”
Section: Nmr Analysis Of V7r- L8a-and L8i-myrmamentioning
confidence: 77%
“…In addition, the relative NOE intensities and cross-peak patterns matched the data obtained for the WT myr(s)MA protein. 27,31 The main differences between the structures are localized within the disordered loop formed by residues Gly-2 -Ser-9. For V7R, the side chain of Arg-7 is poised to make a salt bridge with the side chain of Glu-52, and the mythelene groups of Arg-7 contribute to the hydrophobic interactions with the methylene groups of the myristate ( Figure 6).…”
Section: Structures Of V7r-and L8a-myrmamentioning
confidence: 99%
See 1 more Smart Citation
“…A decade ago, it was proposed that the interaction of the MA domain of Pr55 Gag with membrane is regulated by a myristyl switch (12), and a substantial amount of evidence supports this model (13)(14)(15). Most recently, structural studies from Summers and colleagues (16) demonstrated that the myristate is sequestered when MA is in a monomeric form, which binds membrane poorly. In contrast, when downstream sequences in CA that promote oligomerization are added to MA, the myristate becomes exposed, and membrane binding is substantially increased.…”
mentioning
confidence: 99%